PEMIKIRAN EKONOMI IBN KHALDUN; PENDEKATAN DINAMIKA SOSIAL EKONOMI DAN POLITIK - Aryanti, Yosi (Imara: JURNAL RISET EKONOMI ISLAM, 2018)
Economic activities oriented to the Islamic Economic system are increasingly widespread invarious countries, including Indonesia. Speaking of Islamic Economic theory, it cannot be separated fromthe thoughts of figures who have contributed to the foundation and principles of Islamic economics. IbnKhaldun is one of the greatest scholars who have made a significant contribution to economic development.This figure cannot be separated from the Islamic values. Through deep and critical discussion of his work,it will be seen in the ethical view of religion that accommodates the teachings of Islamic economics, andthe other side of the human family to recognize nature to pursue economic activities.This type of researchis library research. Data were analyzed through a philosophical approach and described deductively. Thisstudy aims to reveal the contribution of Ibn Khaldun?s thoughts on the development of Islamic Economicslike market mechanisms, profits, division of labor and international trade, public finance, state wealthstandards, the concept of money and welfare the community.